Development of carbon nanotubes for field emission application - Huang, Zhangqin (2016)
Four Carbon Nanotubes (CNTs) samples were grown by Thermal Chemical Vapor Deposition (TCVD) using 4 different growth times of 2, 4, 6, and 8 min. Randomly aligned CNTs were obtained. The height of the obtained CNT films varies from 0.71µm at 2 min to 2.51µm at 8 min. Raman spectrum of the CNT grown for 8 min shows higher I_D/I_G ratio of 1.298 compared to 1.106 for 2 min growth time. Field emission characteristics of the CNT with 2 min growth time achieved higher turn-on E-field and maximum current density of 1 V/µm and 20.7mA/cm2 respectively. The result suggested that the field emission characteristics of CNT depend simultaneously on both CNT height and structural properties.